Comparative Evaluation of Microleakage in High Copper Amalgam Restorations using various Adhesive Liners in Permanent Teeth - Shazia Naz; Asdaq Hussain; Nazia Bashir (University of Lahore, 2024)
Objective: To evaluate the microleakage in four commonly used adhesives and high copper amalgam restorations and to determine the best adhesive and alloy combination with least microleakage for a long-lasting restoration. Methodology: This study was conducted on a sample of 80 patients after obtaining the ethical approval. 320 standardized Class I cavities were prepared in premolars indicated for extraction as part of orthodontic treatment. Various combinations of adhesive liners and high copper amalgam alloys were used to restore the cavities in vitro. Adhesive liner was applied in accordance with the manufacturer's instructions, and the cavities were subsequently filled with four different alloys. On the basis of adhesive liners used, four groups (n = 20) were formed randomly (Group A-Amalgam bond Plus, Group B-Scotch bond Multipurpose Plus, Group C-All bond 2 and Group D-Panavia EX). Four premolar teeth (one from each quadrant) were restored with one of four different amalgam alloys: Orosphere Plus, Indiloy, Oralloy or Galloy while the liner was kept same. Three months after their placement in vivo, ten patients were examined from each group, while the remaining ten were examined after six months for microleakage evaluation after extraction of the restored teeth. Quantitative microleakage was assessed as micrograms of dye per tooth through spectrophotometric analysis. Statistical analyses were performed with one way ANOVA and post-hoc Tukey tests at 5% level of significance. Results: Among adhesives used, Amalgam bond Plus demonstrated least microleakage followed by Scotch bond Multipurpose Plus, No significant difference (p>0.05) was found in the degree of microleakage at three months and six months among all the 4 tested groups. Conclusion: Indiloy and Amalgam bond Plus showed the best combination of alloy and adhesive in resisting microleakage. Bonded amalgam restorations have the ability to serve for the longer period of time successfully.